Performance evaluation and enhancement of massive MIMO communication systems - Tran, Xuan Tuong (2017)
The increasing popularity of smart terminals and their multimedia applications, as well as social networks, leads to tremendous growth in demands for capacity and quality of service (QoS) in cellular networks. To meet these demands, multiple-input multiple-output (MIMO) wireless systems have been developed and they are now a part of current standards such as IEEE 802.11 and the fourth generation (4G) long term evolution (LTE). However, there are several challenges, i.e., spectral crisis, spectral efficiency (SE) and high energy consumption, which cannot be accommodated by current generation networks. The capacity of 4G networks with current technologies is reaching theoretical limit soon. Therefore, we focus on performance analyses and enhancement of massive MIMO system, which is considered as a potential technology for future wireless and mobile communication systems.